2018
DOI: 10.2298/tsci160102287r
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer analysis on MHD blood flow of Casson fluid model due to peristaltic wave

Abstract: In this article, heat and mass transfer analysis on MHD blood flow of Casson fluid model due to peristaltic wave has been investigated. The governing equations of blood flow for Casson fluid model, temperature, and energy equation have been solved by taking the assumption of long wavelength and neglecting the inertial forces. The resulting coupled differential equations have been solved analytically and the exact solutions are presented. The impact of various pertinent parameters is plotted and discussed. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Many modern chemical pumps and biomedical devices have been designed by using the peristaltic mechanism, i.e., diabetic pumps, heart-lung machines, waste migration control pumps, pharmacological drug delivery systems, finger and roller pumps. Due to these important practical applications researchers have put their attention toward peristaltic flows [6][7][8][9][10][11][12]. Nanofluids are fluids containing nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Many modern chemical pumps and biomedical devices have been designed by using the peristaltic mechanism, i.e., diabetic pumps, heart-lung machines, waste migration control pumps, pharmacological drug delivery systems, finger and roller pumps. Due to these important practical applications researchers have put their attention toward peristaltic flows [6][7][8][9][10][11][12]. Nanofluids are fluids containing nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…2B pp. 1407-1422 [11], many researchers have discussed the peristaltic flows of Newtonian and non-Newtonian fluids with different flow geometries [12][13][14][15][16]. Most of these investigations are restricted to the peristaltic flow only in a symmetric channel, tube and cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Mabood et al [18] studied the linear viscoelastic fluid model on stagnation point flow on a stretching /shrinking plate and the stagnation point flow with heat transfer and MHD on a stretched surface with the impact of chemical reaction and transpiration. Moreover, distinct investigators examined the stagnation point flow along various geometrical aspects can be found from the references [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%